The Death Penalty and Discretion: Implications of the Furman Decision for Criminal Justice - Riedel, Marc (1976)
Whether the deatn penalty should remain as a penalty available in American criminal law continues to be a subject of controversy among social scientists, lawyers, the judiciary and the public. While the traditional areas of debate over whether the death penalty is a deterrent and whether it is imposed ina discriminatory manner continue to be important issues, the recent Supreme Court decision (Furman v Georgia, 1972) and subsequent legislation has introduced another dimension: the nature and use of discretion. Current litigation on the death penalty (Fowler v North Carolina, 1974) is directed toward a resolution of issues raised by Furman. However, it is our contention that the results of such efforts will raise a range of policy questions regarding how discretion can be exercised not only in other parts of the criminal justice process, but for non-death penalty offenses as well. The purpose of this paper is to examine the Furman decision and subsequent legislation and show that the questions raised about discretionary decisions are questions that are equally applicable to processing all criminal offenses